Assessment of education types for university education via multi-criteria decision-making methods - Soydan, Mehmet; Topcu, Yusuf Ilker (PAMUKKALE UNIV, 2025)
Traditional face-to-face education has been applied as the primary method for centuries in universities, but synchronous distance education and blended education have become increasingly popular in recent decades. Students, academicians, and university administrators are the main stakeholders in university education. This study is the first to use multi-criteria decision-making (MCDM) to determine the best education type, considering these three stakeholder groups. Criteria were identified through a literature review, and stakeholders completed three questionnaires to finalize criteria, compare them pairwise, and rate alternatives. The Analytical Hierarchy Process (AHP) and Criteria Importance Through Inter-criteria Correlation (CRITIC) methods were applied to prioritize criteria, and Visual PROMETHEE was used to rank alternatives. As a result of the calculations traditional face-to-face education was found as the most appropriate in 5 out of 6 cases across the three stakeholder groups. Therefore, face-to-face education should remain integral to university education. If synchronous distance education is offered as a separate program alongside traditional faceto-face education, they should not be considered equivalent, and distinct diplomas should be awarded.
Keywords: Evaluation of education types; AHP; CRITIC; Multi-Criteria decision-making; DISTANCE; SELECTION; Engineering